An epidemic context elicits more prosocial decision-making in an intergroup social dilemma - Magdalena Rychlowska; Job van der Schalk; Antony S. R. Manstead (Scientific Reports, 2022)
Abstract Societal challenges such as the COVID-19 pandemic have the quality of a social dilemma, in that they compel people to choose between acting in their own interests or the interests of a larger collective. Empirical evidence shows that the choices people make in a social dilemma are influenced by how this decision is framed. In four studies, we examined how context of an epidemic influences resource allocation decisions in a nested social dilemma task, where participants share resources between themselves, their subgroup, and a larger collective. Participants consistently allocated more resources to the collective in the context of the Ebola epidemic than in the context of a neighborhood improvement project, and these choices were strongly associated with prescriptive social norms. Together, the findings provide an experimental demonstration that the context of a quickly spreading disease encourages people to act more prosocially.